Multiscale climate emulator of multimodal wave spectra: MUSCLE‐spectra. Issue 2 (21st February 2017) - Rueda, Ana; Hegermiller, Christie A.; Antolinez, Jose A. A.; Camus, Paula; Vitousek, Sean; Ruggiero, Peter; Barnard, Patrick L.; Erikson, Li H.; Tomás, Antonio; Mendez, Fernando J.
Abstract: Characterization of multimodal directional wave spectra is important for many offshore and coastal applications, such as marine forecasting, coastal hazard assessment, and design of offshore wave energy farms and coastal structures. However, the multivariate and multiscale nature of wave climate variability makes this complex problem tractable using computationally expensive numerical models. So far, the skill of statistical‐downscaling model‐based parametric (unimodal) wave conditions is limited in large ocean basins such as the Pacific. The recent availability of long‐term directional spectral data from buoys and wave hindcast models allows for development of stochastic models that include multimodal sea‐state parameters. This work introduces a statistical downscaling framework based on weather types to predict multimodal wave spectra (e.g., significant wave height, mean wave period, and mean wave direction from different storm systems, including sea and swells) from large‐scale atmospheric pressure fields. For each weather type, variables of interest are modeled using the categorical distribution for the sea‐state type, the Generalized Extreme Value (GEV) distribution for wave height and wave period, a multivariate Gaussian copula for the interdependence between variables, and a Markov chain model for the chronology of daily weather types. We apply the model to the southern California coast, where local seas and swells from both the Northern and Southern Hemispheres contribute to the multimodal wave spectrum. This work allows attribution of particular extreme multimodal wave events to specific atmospheric conditions, expanding knowledge of time‐dependent, climate‐driven offshore and coastal sea‐state conditions that have a significant influence on local nearshore processes, coastal morphology, and flood hazards. Key Points: A statistical downscaling framework based on weather types to predict multimodal wave spectra This model can help to characterize the stochastic behavior of the time‐dependent boundary conditions needed for coastal impact studies